Reducing Selenoprotein F Promotes the Transformation of Immortalized Prostate Epithelial Cells. (29th May 2020) - Hong, Lenny; Elhodaky, Mostafa; Kadkol, Shrinidhi; Diamond, Alan
Abstract: Objectives: Selenoprotein F (SELENOF) levels are responsive to available dietary selenium and found in high levels in benign prostate cells. It is implicated in prostate cancer (PCa) mortality due to associations between polymorphisms in the corresponding gene and death from the disease. SELENOF levels are dramatically lower in prostate cancer compared to adjacent benign tissue. The objective of this study was to determine whether reducing SELENOF levels in human, non-transformed RWPE-1 prostate epithelial cells alters their phenotype to implicate SELENOF loss in PCa progression. Methods: SELENOF levels were reduced in RWPE-1 cells that express high levels of SELENOF using a SELENOF shRNA construct. Proliferation was determined by quantifying DNA using fluorometric dsDNA quantitation. Growth in soft agar and cell mobility of cells in culture (wound healing assay) were imaged using an Evos FL microscope and quantified using Image J software. The oxygen consumption rate (OCR) was measured using a Seahorse XFe24 Analyzer. Results: SELENOF levels were reduced in RWPE-1 and these cells exhibited decreased contact inhibition in culture (n = 3, P  < 0.001) when compared to controls. Normal prostate epithelial cells are atypical in that they rely on glycolysis for energy production, have a truncated TCA cycle, and a metabolic shift from glycolysis to oxidative phosphorylation (OXPHOS) occurs in PCa. Reducing SELENOF in RWPE-1 cells resulted in higher OCR compared to controls, indicating that SELENOF can impact the sources and pathways used in cellular energy metabolism. Conclusions: Reduced SELENOF levels in RWPE-1 prostate cells resulted in properties consistent with a transformed phenotype and an increase in OCR, and indicating that the reduction in SELENOF may contribute a metabolic shift towards a PCa cancer-like metabolism. Together, these results indicate that SELENOF loss likely contributes to cancer progression. Funding Sources: This work was supported by a grant from the Department of Defense to AMD and a Pre-Doctoral Education for Clinical and Translational Scientists Fellowship to LKH.